A Study on The Implementation of Picture Word Inductive Model Teaching Writing - Andi Mutmainna; Sriati Usman; Budi Budi (Jurnal Syntax Admiration, 2025)
The study employs a library research design by collecting and analyzing data from previously published sources. It aims to describe the steps in implementing the Picture Word Inductive Model (PWIM) strategy for teaching writing and to explain its effectiveness in improving students' writing skills. Primary data were obtained from Emily F. Calhoun's book (1999), while secondary data were gathered from six journal articles published between 2017 and 2021 on PWIM's implementation in teaching writing. The study identifies 10 steps in implementing the PWIM strategy: selecting and identifying pictures, creating a picture-word chart, reading and reviewing the chart aloud, reading and classifying words, spelling words, adding words, creating titles, generating sentences and paragraphs, and reviewing sentences and paragraphs. However, variations in these steps were observed in the reviewed studies, with adaptations made to accommodate students’ age, knowledge, and learning environment. All studies reported an improvement in students' ability to write descriptive texts when using PWIM. Its effectiveness is attributed to the use of engaging pictures that stimulate inductive thinking and motivate students to actively participate in the learning process. The study has several implications. Teachers should be creative in selecting pictures as learning media to optimize PWIM's impact. For schools, PWIM can support effective teaching and learning activities. At the student level, the strategy is applicable across educational levels for teaching writing skills. Regarding writing itself, PWIM provides visual stimuli that enhance students’ achievement. In conclusion, the study highlights the significance of PWIM as an effective strategy in teaching writing, offering insights into its potential for improving students' writing skills